Pendampingan UMKM : Pembuatan NIB, Branding, dan Digitalisasi Keuangan di Desa Karangsetia (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This community service program was carried out by students of Universitas Pelita Bangsa in Karangsetia Village, Karang Bahagia District, Bekasi Regency, as a concrete effort to strengthen the capacity of micro, small, and medium enterprises (MSMEs) in facing the challenges of digitalization. MSMEs in this area still encounter various obstacles, such as the absence of formal business legality, limited understanding of branding strategies, and minimal utilization of digital technology for both marketing and payment systems. These conditions have weakened business competitiveness and hindered the growth of local enterprises. The program focused on three interrelated aspects: legal compliance, brand development, and digital adoption. Business legality was facilitated through the issuance of the Business Identification Number (NIB), which provides legal certainty while granting access to government programs and financial institutions. Branding was strengthened by designing logos, banners, and simple promotional media to enhance business identity, professionalism, and consumer appeal. Digitalization was promoted through business registration on Google Maps to improve visibility, and the adoption of the Quick Response Code Indonesian Standard (QRIS) as a cashless payment method that is efficient, secure, and widely accepted. The methods employed included observation, socialization, mentoring, and participatory evaluation with business owners. The results demonstrated significant progress, as most MSMEs successfully obtained legal registration, adopted QRIS in daily transactions, registered their businesses on Google Maps, and developed clearer visual identities. This program had a positive impact by increasing entrepreneurial confidence, expanding market reach, and fostering awareness of the importance of digital transformation. Overall, the community service program contributed to strengthening the competitiveness, sustainability, and independence of MSMEs in Karangsetia Village, while supporting the development of the local economy.